Factors affecting the preparation of Cilnidipine nanoparticles - Alzalzalee, Ruaa; Kassab , Hanan (Iraqi Journal of Pharmaceutical Sciences, 2023)
Cilnidipine is a dihydropyridine calcium channel blocker used to improve the neurological outcome following subarachnoid hemorrhage. It belongs to BCS class II drugs that have a low oral bioavailability of 13%, thus preparation as nanoparticles would be expected to improve bioavailability.The aim of the study is to prepare Cilnidipine as nanoparticles using different carriers and co-carriers, concentrations, and types.Cilnidipine nanoparticles were prepared by a solvent anti-solvent method using different carriers (Soloplus®, Poloxamer 188, PVA cold) with co-stabilizers (PEG200, glycerol) at different ratios.Based on the obtained results, formula N4, which included Soloplus in a 1:1:1 weight ratio of drug to the polymer to co-stabilizer, exhibited a particle size of 88.89 nm when stirred at 1000 rpm with an injection speed of 1 ml/min. The polydispersity index (PDI) for this formula was measured at 0.2413. Furthermore, formula N4 demonstrated an impressive 92.2% drug content and an entrapment efficiency (EE) of 95.8%, giving 100% release in 30 min.